PICC catheterization and maintenance for severely and critically ill patients with COVID-19 in the isolation ward (隔离病房重型和危重型新型冠状病毒肺炎患者PICC置管管理) - HAN Huishan (韩会山); LI Naxin (李纳新); LYU Yuan (吕源); LI Yuhua (李玉华); LI Yali (柳雅立) (中西医结合护理)
To implement standardized protective measures and to evaluate the safety and effectiveness of peripherally inserted central venous catheter (PICC) for severely and critically ill patients with COVID-19 in the isolation ward. PICC catheterization was performed to 9 patients who were diagnosed with COVID-19 and treated in the isolation ward. These patients were all given standardized protective measures during the PICC operation. The one-time success rate of catheterization was 100. 00%. There was no postoperative complications such as infection, bleeding, phlebitis, thrombosis, and no nosocomial infection occurred. The implementation of PICC catheterization in severely and critically ill patients in the isolation ward is safe and effective, and standardized protection in catheterization can effectively reduce the risk of cross-infection in hospital. (通过实施规范化防护措施, 评估经外周静脉置入中心静脉导管(PICC)在隔离病房收治的重型和危重型新型冠状病毒肺炎患者中应用的安全性和有效性。回顾隔离病房接受诊治的9例确诊/疑似患者的临床资料, 患者接受PICC置管术, 且术中实施规范化防护措施。9例患者均一次置管成功, 术后未发生感染、出血、静脉炎、血栓等并发症; 无一例置管患者和医务人员发生院内感染。隔离病房收治的重型和危重型新型冠状病毒肺炎患者中实施PICC置管安全、有效, 置管中规范化防护可以有效避免院内交叉感染的发生。)